Zhuangzi's idea of 'spirit': acting and 'thinging things' without self-assertion. Issue 1 (2nd January 2016) - Chiu, Wai Wai
ABSTRACT: In contrast to his contemporaries who take the heart–mind as the ruler of a person, Zhuangzi suggests that one's action is guided by the spirit (shen 神). Questions arise as one articulates the function of spirit and its relationship with the heart–mind. In this article, I articulate the relationship between heart–mind and spirit to show three points: first, spirit is a kind of qi 氣 that can be tied or run smoothly, or rather the mechanism triggered by the functioning of smooth qi. This reading brings the skill passages together with the fasting of heart–mind ( xin zhai 心齋) passage. Second, the proceeding of spirit admits no fixed ways and is not confined to any particular organ or faculty, so it avoids the problem of self-assertion mentioned in Qiwulun. Third, the proceeding of spirit implies that one's practice takes as many particularities of the context as possible into account, so the person has a higher chance to reduce conflict in interacting with things and other people and bring out their potential. This is a reason why skilful practices are related to Zhuangzi's ideal of nourishing life, both physiologically and psychologically.